Calcium channel blocker use is associated with lower fasting serum glucose among adults with diabetes from the REGARDS study. (May 2016) - Khodneva, Yulia; Shalev, Anath; Frank, Stuart J.; Carson, April P.; Safford, Monika M.
Highlights: Diabetes does not have a definitive treatment, but in recent studies of mouse models of type 1 diabetes, verapamil, a commonly used medication for a variety of conditions, decreased β-cell apoptosis and restored insulin levels, essentially rescuing mice from the disease. The role of verapamil as a possible anti-diabetic agent in humans is highly novel and unexplored. Verapamil use was associated with significantly lower fasting blood glucose levels among participants with diabetes from a population-based cohort, controlling for a host of covariates. Abstract: Background: Ca 2+ channel blockers (CCB) and verapamil in particular prevented β-cell apoptosis and enhanced endogenous insulin levels in recent studies of mouse models of diabetes. Verapamil's effect on serum glucose levels in humans with diabetes is not described. Methods: We used data from the REasons for Geographic and Racial Differences in Stroke (REGARDS), a national cohort study of community-dwelling middle-aged and older adults, enrolled between 2003 and 2007 from the continental United States. We examined associations of CCB and verapamil use with fasting serum glucose among 4978 adults with diabetes, controlling for covariates in generalized linear models (GLM). Findings: The sample included 1484 (29.6%) CCB users, of which 174 (3.4%) were verapamil users. In fully adjusted GLMs, CCB users had 5 mg/dL lower serum glucose compared to non-users. Verapamil users had on average 10 mg/dL lower serum glucose compared to CCB non-users with substantially greater differences among insulin users: 24 mg/dL lower serum glucose among users of insulin in combination with oral agents and 37 mg/dL lower among users of insulin alone. Interpretation: CCB and in particular verapamil use was associated with lower fasting blood glucose levels among REGARDS participants with diabetes. Funding: UO1NS041588 from theNational Institute of Neurological Disorders and Stroke, NIH ;K24HL111154 andR01HL080477 from theNational Heart, Lung, and Blood Institute .